2013
DOI: 10.1044/1092-4388(2012/11-0303)
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in Delayed Auditory Feedback Effects on Speech Fluency and Rate in Normally Fluent Adults

Abstract: Individual variability in response to DAF may be accounted for by subgroups of individuals. This suggests that certain normally fluent individuals could be more dependent on intact feedback to maintain fluency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 68 publications
7
31
0
2
Order By: Relevance
“…These results reinforce reports from students who described difficulties in speaking fluently with DAF (15,28) . In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2).…”
Section: Discussionsupporting
confidence: 81%
“…These results reinforce reports from students who described difficulties in speaking fluently with DAF (15,28) . In the intergroup comparison of spontaneous speech, there were more differences in Non-Altered Auditory Feedback condition than in the delayed one (Tables 2).…”
Section: Discussionsupporting
confidence: 81%
“…The interaction between the auditory aspects and the speech fluency has been demonstrated in the literature [17][18][19][20][21] , arousing thus the interest among researchers about the topic of stuttering and hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in fluent individuals have shown that delayed auditory feedback (DAF) has caused difficulties in speech fluency [16][17][18][19][20][21][22] , and decrease in speech rate [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there is evidence that prelingual deaf children have problems in developing intelligible speech skills (Oller & Eilers, 1988) and that speech production of children with cochlear implants, who receive better auditory input, is often more adequate than that of children with strong hearing loss using hearing aids (Baudonck, Dhooge, D'haeseleer, & Van Lierde, 2010). Several studies have shown that delaying auditory feedback or masking auditory feedback by noise affects speech production both in typical (Amazi & Garber, 1982;Chon, Kraft, Zhang, Loucks, & Ambrose, 2012;Sasisekaran, 2012) and clinical populations (Hudock & Kalinowski, 2014).…”
Section: Phonological Representations and The Role Of Altered Auditormentioning
confidence: 99%